PEMBERESAN HARTA PAILIT DEBITOR YANG MENJADI OBJEK SITA PADA PERKARA PIDANA (STUDI KASUS PERKARA NO. 11/PDT.SUS-GUGATAN LAIN-LAIN/2018/PN.JKT.PST) - Triardi, Dani (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
It is not impossible for legal subject such as an individual or entity that is in the process of bankruptcy, to be processed simultaneously with a criminal case. This raises the possibility that the assets of the bankrupt debtor in the bankruptcy process, which should be under the control of the Curator, will also be the object of confiscation in a criminal case. However, the laws and regulations have not explicitly accommodated the procedures for confiscating and controlling the assets of the bankrupt debtor in the event that there is an overlap of authority between the Curator in the bankruptcy process and the Public Prosecutor in the criminal case process. The purpose of this study is to determine the procedure for settlement of bankrupt debtor assets which simultaneously becomes the object of confiscation of evidence by the Prosecutor for the purposes of a criminal case based on prevailing statutory regulations or legal principles. The research method used is normative, using secondary data, which is obtained from literature research, including primary, secondary and tertiary sources of law. In the event of a condition where the assets of the bankrupt debtor in the bankruptcy process become the object of confiscation in a criminal case at the same time, what must take precedence is a legal process that already has permanent legal force first. If the bankruptcy decision occurs earlier, then control of the debtor's assets will remain under the curator's authority to settle the debt. However, the Public Prosecutor is still unable to impose general confiscation for the state on evidence in the form of assets of a defendant who is a bankrupt debtor, because such assets are entitled to the creditors.